THE ANALYSIS PREDICTOR OF LANGUAGE DEVELOPMENT ACHIEVEMENT IN UNDER FIVE YEAR OLD CHILDREN - Tri Ratna Ningsih; Moh Alimansur; Ifa Roifah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
The difficulty of working mothers in stimulating the development of children's language was the lack of quality time for stimulation, the child was given a